Organizational Capacities for Change : Insights from Finnish Healthcare Reform - Sinervo, Lotta-Maria; Laihonen, Harri; Kork, Anna-Aurora (IKAM - Institute of Knowledge Asset Management, 2024)
Healthcare systems in many countries are under pressure for renewal due, for instance, to demographic changes or service delivery fragmentation. This paper focuses on organizational capacities for change by illustrating knowledge, processes, and resources needed for implementing healthcare reforms at the meso-level organizations. We examine these capacities in the empirical context of the Finnish healthcare reform to find out how the reform goal of fostering social impact in policy documents is expected to be operationalized and managed in the newly established “Wellbeing Services Counties”. In our paper, we present four organizational capacities for making social impact: 1) systematic use of effectiveness information in knowledge management, 2) holistic evaluation and measurement system supporting for managing effectiveness, 3) effectiveness as a key principle in resource allocation, and 4) translation of reform policy objectives into organizational goals. However, to achieve the goals and understand the desired change at the level of organizational action, collective sensemaking of social impact would be needed in aligning different interpretations and effective organizational practices. We call for more collective knowledge formation processes in transforming reform objectives into organizational activities to make a social impact.
Keywords: Healthcare reform; organizational capacity; public management; knowledge management; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|